2019
DOI: 10.1002/cctc.201900334
|View full text |Cite
|
Sign up to set email alerts
|

CuZn Catalysts Superior to Adkins Catalysts for Dimethyl Adipate Hydrogenolysis

Abstract: Industrial hydrogenolysis of esters to alcohols relies on the use of Adkins catalysts whose production and disposal is an environmental burden. This work is focused on CuZn catalysts that represent an ecological alternative to Adkins catalysts. Four CuZn catalysts with Cu/Zn atomic ratio ranging from 0.5 to 2.0 and single phase CuO and ZnO catalysts were prepared by co‐precipitation and their hydrogenolysis activity was compared with a commercial Adkins catalyst. Dimethyl adipate was used to test the catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…We also calculated the turnover frequency (TOF) value of 31.5 h −1 for the Cu/Ti(0.4)-SiO 2 catalyst, which are higher than the reported TOF value of 15.1 h −1 for CuZn catalyst. [46] The H 2 /DMA ratio affects the selectivity of the product and varying the H 2 /DMA ratio can produce the product with one ester group hydrogenated (Figure S13, Supporting Information). Moreover, except DMA, the Cu/Ti(0.4)-SiO 2 can also catalyze the dimethyl oxalate (DMO) hydrogenation to EG (Figure S14, Supporting Information).…”
Section: Catalytic Performance In Dma Hydrogenationmentioning
confidence: 99%
“…We also calculated the turnover frequency (TOF) value of 31.5 h −1 for the Cu/Ti(0.4)-SiO 2 catalyst, which are higher than the reported TOF value of 15.1 h −1 for CuZn catalyst. [46] The H 2 /DMA ratio affects the selectivity of the product and varying the H 2 /DMA ratio can produce the product with one ester group hydrogenated (Figure S13, Supporting Information). Moreover, except DMA, the Cu/Ti(0.4)-SiO 2 can also catalyze the dimethyl oxalate (DMO) hydrogenation to EG (Figure S14, Supporting Information).…”
Section: Catalytic Performance In Dma Hydrogenationmentioning
confidence: 99%
“…For the gas‐phase route, copper‐based catalysts have been studied for decades . Violetta found that Cu−Zn was better than conventional Cu−Cr due to its higher dispersion and stability in hydrogenation environment. And a highest DMA conversion of about 97 % was achieved with HDO selectivity below 80 %.…”
Section: Figurementioning
confidence: 99%
“…Our previous work reported a novel hierarchical porous copper catalyst (Cu/HPS) for the reaction with an extremely high space‐time yield (STY) of hexanediol (0.72 h −1 ) and HDO selectivity of 89 %, which was attributed to highly dispersed Cu 0 and Cu + species as well as the enhanced mass‐transfer due to the ordered mesoporous structure. Up to now, the bottleneck problem of the gas‐phase hydrogenation of DMA is mainly the selectivity of HDO . In addition, the essential high ratio of H 2 /diester (generally, higher than 100) leads to high energy consumption.…”
Section: Figurementioning
confidence: 99%
“…into a solution containing one or more metal ions, and maintain a certain temperature so that the solution enters the pores of the carrier. [28][29] The precipitation method is used to manufacture catalysts that require high dispersion and contain one or more metal oxides. When manufacturing multi-component catalysts, suitable precipitation conditions are very important to ensure the uniformity of product composition and to manufacture high-quality catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The impregnation method is to immerse a carrier with high porosity (such as diatomaceous earth, alumina, activated carbon, etc.) into a solution containing one or more metal ions, and maintain a certain temperature so that the solution enters the pores of the carrier [28–29] . The precipitation method is used to manufacture catalysts that require high dispersion and contain one or more metal oxides.…”
Section: Introductionmentioning
confidence: 99%